Lean‐season primary productivity and heat dissipation as key drivers of geographic body‐size variation in a widespread marsupial. Issue 1 (21st April 2015) - Correll, Rachel A.; Prowse, Thomas A. A.; Prideaux, Gavin J.
Abstract : Geographic body‐size variation characterises many mammal species. Hypotheses centring around heat conservation, heat dissipation, primary productivity and seasonality have been advanced to explain geographic body‐size patterns. However, identification of the primary body‐size drivers has often been hampered by a paucity of data for broadly distributed species and the application of regression models that have not explicitly accounted for the spatial clustering inherent in such datasets. We used Australia's most widespread marsupial, the common brushtail possum Trichosurus vulpecula, as a model species with which to test five proposed drivers of geographic body‐size variation. Using geo‐referenced skull measurements from 588 specimens and a suite of putative environmental covariates, we employed spatial simultaneous autoregressive models, together with information criteria, to evaluate these different hypotheses. Our analysis identified a strong, positive relationship between possum body size and primary productivity during the least productive season, whereas the relationship with mean annual productivity received less support. Consistent with the heat‐dissipation hypothesis, T. vulpecula body size also decreased with increasing mean summer maximum temperature. Spatial autoregression coefficients estimated from the simultaneous autoregressive models were always high, suggesting that additional abiotic or biotic factors might contribute to the spatial patterns observed. We argue that the analysis of geographic body‐size variation should consider multi‐causal possibilities rather than treating the numerous hypotheses as competing, mutually exclusive alternatives.